PERAN MOTIVASI INTRINSIK DAN MOTIVASI EKSTRINSIK SEBAGAI PEMODERASI PADA PENGARUH KEPEMIMPINAN TERHADAP KINERJA KARYAWAN (Studi pada Karyawan BPR di Wilayah Kabupaten Karanganyar) - Praptiestrini .; Rohwiyati . (Universitas Sahid Surakarta, 2020)
This research aims to analyses (1) significance effect of leadership and motivation on employee performance (2) effect of leadership on employee performance moderated of motivation. This research using samples of 78 employees at BPR in Karanganyar District with purposive sampling technique. To test the hypothesis using multiple regression analysis and moderating regression analysis. The result shows that (1) leadership and motivation have significance effect on employee performance (2) motivation moderates the effect of leadership on employee performance.